Unraveling the signaling pathways of plant cold stress: current insights and future directions - Peng, Chen; Hua, Wei; Liu, Jing (Frontiers in Plant Science, 2025)
Cold stress is a major abiotic stress that seriously hinders plant growth and development, ultimately affecting crop yields. During the process of evolution, plants have evolved sophisticated adaptive strategies encompassing acclimation processes and tolerance mechanisms. Over the past two decades, substantial research breakthroughs have been made in elucidating the core components and complex regulatory networks underlying cold tolerance. This review systematically synthesizes the recent progress in three fundamental aspects: cold stress perception and signal transduction pathways, downstream physiological and molecular responses, and the pivotal regulatory roles of transcription factors (particularly CBF/DREB1 family) and cold-responsive miRNAs. In addition, we also investigated the intricate crosstalk between cold response and other biological processes including photoperiod sensing, flowering regulation, circadian rhythm, phytohormone signaling, and the dedicated discussion addresses how plants achieve metabolic and developmental trade-offs when allocating resources between cold defense and other vital traits. Looking forward, we propose four promising research directions: identifying novel cryo-sensors beyond currently known receptors, post-translational modification dynamics of CBF proteins, homeostatic control mechanisms among competing regulatory factors, and translational applications of cold stress pathways in precision breeding programs. Addressing these knowledge gaps will not only deepen our understanding of plant cold adaptation at molecular level, but also facilitate the development of climate-resilient crops through molecular design breeding.